Who Gets the Message? Heat-Health Communication by Australian State and Territory Health Departments - Manoj Bhatta; David Karacsonyi; Linda Ford; Kerstin K. Zander; Supriya Mathew (International Journal of Environmental Research and Public Health, 2026)
Extreme heat causes more deaths in Australia than any other natural hazard, yet the consistency and inclusivity of heat-health messaging by Australian state and territory health departments have not been systematically assessed. This study compared heat-health communication across all Australian jurisdictions using official health department websites (n = 8) and corresponding Facebook pages, from which 374 posts were analysed. Website content was examined comparatively across jurisdictions, while Facebook messaging was analysed across two key periods: the 2019–2020 Black Summer and the 2024–2025 summer. Using comparative qualitative content analysis, we examined message content, inclusivity, geographic specificity, and communication approaches for vulnerable populations. Substantial variation was observed across jurisdictions and over time. During 2019–2020, messaging showed a predominantly reactive pattern in the context of concurrent hazards, particularly bushfires and COVID-19. By 2024–2025, communication showed a more anticipatory pattern, with some jurisdictions adopting clearer heat-specific terminology, visual warning symbols, regionally targeted communication, and multilingual resources. However, no jurisdiction provided Indigenous-language translations or culturally tailored messaging for remote Indigenous communities, and limited attention was given to indoor heat exposure, power outages, and remote populations. These findings highlight the need for more coordinated, equitable, and context-specific heat-health communication strategies to strengthen climate adaptation and public health preparedness in Australia.